Stolen goods markets and criminal redistribution in Enugu state of Nigeria - Ugwuoke, Christopher U. (Crime, law and social change, 2023)
This study offers an insightful criminological literature on stolen goods market. The existence of markets for stolen goods is not of a recent development. In recent times however, such markets have become important aspects of the network of organized crimes that have impacted negatively on both domestic and global economic development. Qualitative approach was employed to obtain information from a sample of 306 respondents comprising traders [N = 300] and 6 officers of the criminal justice system respectively. The study found that stolen goods markets favour the increasing rate of theft, pilfering, shoplifting, burglary and lone ranger crimes in the state. This study concludes that patronage of stolen goods is desirable to many because it offer cheaper alternatives to regular prices of goods in the conventional market. The study recommends formulation of policies in areas of social development, open market regulation, building public trust with law enforcement agents and community policing.